18 F-FDG Positron Emission Tomography in Multifocal Pyomyositis - C. N. B. Harisankar; B. Mittal; R. Kashyap; A. Bhattacharya; S. Singhi (World Journal of Nuclear Medicine)
18 F-Fluoro-deoxyglucose-positron emission tomography/computed tomography findings in a case presenting with pyomyositis are presented in this report.